Theory of a resonantly interacting impurity in a Bose-Einstein condensate - Drescher, Moritz; Salmhofer, Manfred; Enss, Tilman (Physical review research, 2020)
We investigate a Bose-Einstein condensate in strong interaction with a single impurity particle. While this situation has received considerable interest in recent years, the regime of strong coupling remained inaccessible to most approaches due to an instability in the Bogoliubov theory arising near the resonance. We present a nonlocal extension of the Gross-Pitaevskii theory that is free of such divergences and does not require the use of the Born approximation in any of the interaction potentials. We find a new dynamical transition regime between attractive and repulsive polarons, where an interaction quench results in a finite number of coherent oscillations in the density profiles of the medium and in the contact parameter before equilibrium is reached.